ENERGY EFFICIENCY PROJECTS OF PUBLIC-PRIVATE PARTNERSHIPS IN INVESTMENT AND CONSTRUCTION SPHERE - Natal'ya V Gorodnova; Andrey E. Berezin (Статистика и экономика)
Due to the economic instability the problem of development of mechanisms of integration of state and private business became even more important. The paper presents the evaluation of the effectiveness of public-private partnerships (PPPs). It is concluded that adoption of the new Federal law on PPP will increase the efciency of interaction between participants in PPP projects